2003
DOI: 10.1046/j.1471-1842.2003.00428.x
|View full text |Cite
|
Sign up to set email alerts
|

Non use of health information kiosks examined in an information needs context

Abstract: Whilst great emphasis has rightly been placed on the increased availability and use of health information, little research has been undertaken into the non use of such material, particularly with regard to electronic sources. Computer transactional log data from health information touch screen kiosks, collected as part of an ongoing Department of Health-funded study being carried out by City University, showed that females in the 55-74 age group were particularly under-represented as users. To explore reasons … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
0

Year Published

2005
2005
2011
2011

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 17 publications
1
18
0
Order By: Relevance
“…living with cancer. Williams et al [22], found value also in direct person-to-person communication in their study of touch screen health information kiosks. For the people involved, the first and major source of information was the doctor; other sources were consulted when recommended or provided.…”
Section: Published As: Hardiker Nr Grant Mj Factors That Influence mentioning
confidence: 95%
See 2 more Smart Citations
“…living with cancer. Williams et al [22], found value also in direct person-to-person communication in their study of touch screen health information kiosks. For the people involved, the first and major source of information was the doctor; other sources were consulted when recommended or provided.…”
Section: Published As: Hardiker Nr Grant Mj Factors That Influence mentioning
confidence: 95%
“…This includes interest in one's own health, openness to experience or a belief that information can make a difference to health. In-depth interviews were undertaken with 13 female patients, aged 55-74, attending a GP surgery in Musselburgh, Scotland over two consecutive days, regarding the provision of touch screen health information kiosks within the surgery [22]. Williams et al noted that participants lacked curiosity to use the kiosk,…”
Section: Published As: Hardiker Nr Grant Mj Factors That Influence mentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies have focused on its application to studies of health information. Williams et al (2003) employed the Sense-Making framework to explore the information needs and behaviours of female patients when visiting their GP.. and found few information needs reported by the participants. Often these were dealt with by avoidance, or relying on the instructions given by the doctor.…”
Section: Insert Figure 1 Herementioning
confidence: 99%
“…In other locations, it is possible that people either felt inhibited in using the kiosk or they did not have time to browse, as the purpose of their visit was not to seek information, such as when attending the Asian Women's Project. Such reasons are among those reported by Williams et al (2003) in their survey of non-touchscreen users.…”
Section: Discussionmentioning
confidence: 85%